2022
DOI: 10.1002/ptr.7554
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of molecular targets and mechanisms of Chinese medicinal formula Acacia CatechuScutellariae Radix in the treatment of COVID‐19 by a systems pharmacology strategy

Abstract: Coronavirus disease 2019 (COVID‐19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). In China, the Acacia catechu (AC)‐ Scutellariae Radix (SR) formula has been widely used for pulmonary infection in clinical practice for several centuries. However, the potential role and mechanisms of this formula against COVID‐19 remains unclear. The present study was designed to dissect the active ingredients, molecular targets, and the therapeutic mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Therefore, natural compounds in herbs seem to be rich sources for screening potential drugs against coronaviruses. As expected, several herbal medicines as well as isolated compounds in herbs have been reported to possess inhibitory activities against SARS-CoV-2 in the past few years [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Although herbal medicines and their isolated compounds are not as effective as chemical antiviral drugs, they are empirically safe for the human body, particularly after long-term consumption.…”
Section: Introductionmentioning
confidence: 62%
“…Therefore, natural compounds in herbs seem to be rich sources for screening potential drugs against coronaviruses. As expected, several herbal medicines as well as isolated compounds in herbs have been reported to possess inhibitory activities against SARS-CoV-2 in the past few years [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Although herbal medicines and their isolated compounds are not as effective as chemical antiviral drugs, they are empirically safe for the human body, particularly after long-term consumption.…”
Section: Introductionmentioning
confidence: 62%
“…Further research revealed that seven key active components (chrysin, baicalein, wogonin, apigenin, isoliquiritigenin, isoliquiritin apioside, and Glycyrrhetinic acid) were regarded to be effective on COVID-19, and twelve targets (MAPK3, IL6, JUN, IL2, STAT3, AKT1, TNF, STAT1, EGFR, HSP90AA1, VEGFA RELA) were screened to be effective on COVID-19. Studies have shown that baicalein and apigenin can inhibit the 3C-like protease of SARS-CoV-2 [ 26 ]. Glycyrrhetinic acid has been shown to have anti-COVID-19 activity [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…These medicines are used in various health problems e.g. treatment of chronic liver diseases, pulmonary infection therapy, coronary artery disease treatment and more [98,99,100,101]. Fisetin has so far been poorly studied, however multiple therapeutic effects were postulated.…”
Section: Fisetinmentioning
confidence: 99%